Clonorchis sinensis aggravates biliary fibrosis through promoting IL-6 production via toll-like receptor 2-mediated AKT and p38 signal pathways. - Yuru Wang; Xu Zhang; Xiaocen Wang; Nan Zhang; Yanhui Yu; Pengtao Gong; Xichen Zhang; Yeting Ma; Xin Li; Jianhua Li (Public Library of Science (PLoS), 2023)
Clonorchis sinensis is an important food-borne zoonotic parasite which has been linked to biliary fibrosis and cholangiocarcinoma. However, the details of the pathogenesis of C. sinensis were unclear. To explore the role and regulatory mechanism of toll-like receptor 2 (TLR2) in C. sinensis-induced biliary fibrosis, we established the C. sinensis-infected C57BL/6 mouse model with TLR2-/- and wild type (WT) mice. The mortality rate, liver lesions, TLR2 and TGF-β1 expression, phosphorylation of Smad2/3, AKT, p38, ERK and p65, and cytokine productions were analyzed. Furthermore, similar parameters were examined in mouse biliary epithelial cells (BECs) co-cultured with C. sinensis excretory/secretory proteins (ESPs). The results showed that TLR2 expression was enhanced significantly in C. sinensis-infected WT mice and mouse BECs. C. sinensis-infected TLR2-/- mice exhibited an increased weight and a decreased mortality rate; significantly alleviated liver lesions and biliary fibrosis, reduced numbers of myofibroblasts; decreased expression of TGF-β1 and phosphorylation level of AKT, p38 and Smad2/3; significantly decreased production of IL-6, TNF-α and IL-4, while increased production of IFN-γ compared with C. sinensis-infected WT mice. Furthermore, C. sinensis ESPs could activate TLR2-mediated AKT and p38 pathways to increase the production of IL-6 in mouse BECs. In conclusion, these data indicate that C. sinensis infection activated TGF-β1-Smad2/3 through TLR2-mediated AKT and p38 pathways to promote IL-6 production, which resulted in myofibroblast activation and aggravating biliary fibrosis in mice.